CIA assets and the rise of the Guadalajara connection - Marshall, Jonathan (Crime, law and social change, 1991)
Why do some drug traffickers prosper and grow powerful while others languish behind bars? The answer usually depends less on their ruthlessness than their political protection. That principle holds true on the international level no less than on the domestic level. Since World War II, one of the most critical sources of such institutional protection for the drug trade has been the U.S. Central Intelligence Agency. An ideal illustration of this phenomenon was rise of the Guadalajara Cartel in Mexico, one of the largest drug suppliers to the North American market in the late 1970s and 1980s. Its extraordinary success is explained by its connections first to the Mexican intelligence agency DFS and, through it, to the CIA.